Evolution of Diffusion Tensor Imaging Parameters after Acute Subarachnoid Haemorrhage: a Prospective Cohort Study - Fragata, I (2017)
INTRODUCTION: Few studies assessed diffusion tensor imaging (DTI) changes in the acute phase of subarachnoid haemorrhage (SAH). We prospectively evaluated DTI parameters in the acute phase of SAH and 8-10 days after and analysed whether changes could be related to SAH severity or to the development of delayed cerebral ischemia (DCI). METHODS: Apparent diffusion coefficient (ADC) and fractional anisotropy (FA) changes over time were assessed in a prospective cohort of patients with acute SAH. Two MRI studies were performed at <72 h (MRI-1) and 8-10 days (MRI-2). DTI parameters were recorded in 15 ROIs. Linear mixed regression models were used. RESULTS: Forty-two patients were included. Subtle changes in DTI parameters were found between MRI-1 and MRI-2. At the posterior limb of internal capsule (PLIC), a weak evidence of a 0.02 mean increase in FA (p = 0.064) and a 17.55 × 10-6 mm2/s decrease in ADC (p = 0.052) were found in MRI-2. Both FA and ADC changed over time at the cerebellum (increase of 0.03; p = 0.017; decrease of 34.73 × 10-6 mm2/s; p = 0.002, respectively). Patients with DCI had lower FA values on MRI-1 and lower ADC on MRI-2, although not reaching statistical significance, compared to non-DCI patients. DTI parameters on MRI-1 were not correlated to clinical admission scales. CONCLUSION: ADC and FA values show subtle changes over time in acute SAH at the PLIC and cerebellum although not statistically associated with the severity of SAH or the occurrence of DCI. However, DTI changes occurred mainly in DCI patients, suggesting a possible role of DTI as a marker of DCI.